Importance of Visual Arts in Education: A Challenge in Teacher Formation - Cárdenas-Pérez, Ramón Esteban; Troncoso-Ávila, Andrés (Revista Electrónica Educare, 2014)
This literature review addresses the redefinition of the Visual Arts curriculum as established by the Ministry of Education of Chile, as well as the action-reaction strategies that primary education teachers should consider when teaching different artistic skills to students grades 1 through 6. It is concluded that the proposed Visual Arts curriculum is a powerful educational tool to assist teachers to contextualize arts teaching; help students to express their ideas and emotions based on a critical, reflective, and permanent attitude; and generate opportunities for personal growth focused on the acquisition of creative skills and models of arts education which contribute, as a whole, to the development of human capacities.